2016
DOI: 10.1007/s12010-016-2304-4
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Styrene Monooxygenase for Biocatalysis: Reductase-Epoxidase Fusion Proteins

Abstract: The enantioselective epoxidation of styrene and related compounds by two-component styrene monooxygenases (SMOs) has targeted these enzymes for development as biocatalysts. In the present work, we prepare genetically engineered fusion proteins that join the C-terminus of the epoxidase (StyA) to the N-terminus of the reductase (StyB) through a linker peptide and demonstrate their utility as biocatalysts in the synthesis of Tyrain purple and other indigoid dyes. A single-vector expression system offers a simplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 47 publications
3
39
0
Order By: Relevance
“…Furthermore, the above fusion protein was cloned into a single-vector expression system to couple the epoxidation function to NADH oxidation, thereby enhancing the overall catalytic function of the system. The observed positive changes in the catalytic mechanism were attributed in part to an increased flavin-binding affinity of the StyB reductase associated with its N-terminal extension [160]. In a similar optimization, the NADP(H) dependence of hyperthermophilic 6-phosphogluconate dehydrogenase was engineered to favor the less expensive NAD(H) cofactor for a promising industrial application in bio-batteries [161].…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
“…Furthermore, the above fusion protein was cloned into a single-vector expression system to couple the epoxidation function to NADH oxidation, thereby enhancing the overall catalytic function of the system. The observed positive changes in the catalytic mechanism were attributed in part to an increased flavin-binding affinity of the StyB reductase associated with its N-terminal extension [160]. In a similar optimization, the NADP(H) dependence of hyperthermophilic 6-phosphogluconate dehydrogenase was engineered to favor the less expensive NAD(H) cofactor for a promising industrial application in bio-batteries [161].…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
“…Further comparison with a naturally occurring fused SMO system revealed our artificial Fus‐SMO to be about two orders of magnitude more active. Finally, a recent study showed that another artificially fused SMO showed an epoxidation rate more than five times lower than that of our Fus‐SMO . The different behaviour could be attributed to the different types of linkers used for the fusion.…”
Section: Resultsmentioning
confidence: 97%
“…The styA and styB genes belonging to the bi‐enzymatic system of the SMO from Pseudomonas sp. were genetically fused through a flexible linker, made up of 30 amino acid residues (for details, see Section S4.1 in the Supporting Information). The construct (Fus‐SMO) was designed in the following order: (N‐His 6 ‐tag)‐StyA‐linker‐StyB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations